Taste uncoupled from nutrition fails to sustain the reinforcing properties of food - Jeff A. Beeler; James E. McCutcheon; Zhen Cao; Mari Murakami; Erin Alexander; Mitchell F. Roitman; Xiaoxi Zhuang (2012)
Abstract Recent findings suggest the reward system encodes metabolic value independent of taste, provoking speculation that the hedonic value of taste could be derived from nutritional value as a secondary appetitive property. We therefore dissociated and compared the impact of nutrition and taste on appetitive behavior in several paradigms. Though taste alone induces preference and increased consumption, in the absence of nutritional value its reinforcing properties are greatly diminished and it does not, like sucrose, induce increased responding over time. In agreement with behavioral data, saccharin‐evoked (but not sucrose‐evoked) dopamine release is greatly attenuated following pre‐exposure, suggesting that nutritional value is critical for dopamine‐mediated reward and reinforcement. Further supporting the primacy of nutrition over taste, genetically increased dopaminergic tone enhances incentive associated with nutritional value with minimal impact on taste‐based, hedonic incentive. Overall, we suggest that the sensory‐hedonic incentive value associated with taste functions as a conditioned stimulus that requires nutritional value to sustainably organize appetitive behavior.